Financial Performance Analysis of Dumai City Regional Government Financial Reports - Yuandina Yuandina; Inayati Inayati (Journal La Bisecoman, 2024)
This research is intended to determine the financial performance of the Dumai City Region using analytical techniques in the form of comparative techniques, common size techniques and ratio techniques. The ratio technique uses descriptive formulas including: PAD Effectiveness Ratio, Regional Financial Efficiency Ratio, Harmony Ratio, Spending Pattern Indicator Ratio, Regional Financial Independence Ratio, Solvency Ratio, and Liquidity Ratio. This research is quantitative descriptive in nature by calculating financial data obtained from the Dumai City Regional Government Financial Report for the 2022 fiscal year. The results of research using comparative techniques show that the financial performance of Dumai City in 2022 is quite optimal, at with a percentage of realized income that exceeds the target of 102 .53% and actual expenditure reached 93.55% of the budgeted target. Meanwhile, financial performance using the Common Size Technique shows that the largest income from total Regional Revenue comes from the General Allocation Fund (DAU). Financial Performance on the PAD Effectiveness Ratio indicator is classified as effective, at 102.53%, the Regional Financial Efficiency Ratio (REKD) is inefficient, at 109.99%, the Harmony Ratio is included in the standard category, at 17.27% for capital expenditure, Indicator Ratio Shopping patterns are classified as less efficient, at 43.09%, the Regional Independence Ratio is included in the participatory criteria, at 51.20%, the Solvency Ratio is considered very effective, at 3.83%, and the Liquidity Ratio is classified as very effective, at 2.5–5.61%.